A new species of Ctenocheles Kishinouye, 1926 (Decapoda, Axiidea, Ctenochelidae) from China - Kou, Qi; Poore, Gary C. B.; Li, Xinzheng (Zootaxa, 2024)
A new species of ghost shrimp, Ctenocheles sinicus, is described based on specimens recently collected from Taiwan Strait, the East China Sea, at a depth of 50 m. The new species is characterized by: the dorsally unarmed rostrum attaining one-third the length of the eyestalks; the rounded suborbital angle of the carapace; maxillipeds 2 and 3 each with a short exopod; the merus and ischium of pereopod 1 being unarmed along the lower margin; the major cheliped with fingers twice as long as the palm; the ischium of pereopod 2 armed with prominent spiniform setae along the lower margin; and the rounded anterodistal angle of uropodal exopod. The morphological differences between the new species and other congeners are discussed and a key to the species of Ctenocheles Kishinouye, 1926 is provided. The molecular analyses show signiﬁcant diﬀerences between the new species and two populations of its sympatric congener, Ctenocheles balssi Kishinouye, 1926. The new species is justified and an individual from the Philippines previously identified as C. balssi probably represents an undescribed species.